Intra- and interindividual correlations between auditory evoked potentials and speech perception in cochlear implant users. - Makhdoum MJ; Groenen PAP; Snik FM; van den Broeck P (Scandinavian Audiology, 1998)
Several electrophysiological techniques have been used to supplement behavioural measurements in the evaluation of the benefit of cochlear implantation, namely the electrically evoked auditory brainstem response (EABR), electrically evoked middle latency response (EMLR) and electrically evoked late latency response (EALR). To study the interdependence of these responses, the present paper deals with a combination of EABR, EMLR and EALR measurements obtained from 15 postlingually deaf subjects implanted with the Nucleus multichannel device at the University Hospital Nijmegen. In particular, we investigated whether there were intercorrelations between amplitude and latencies of the evoked potential peaks and/or correlations with long-term speech perception scores. Significant correlations were found between the peak V amplitude of the EABR and the NaPa and NbPb amplitudes of the EMLR. No significant correlation was found between the EABR and EMLR amplitudes on the one hand and EALR peak amplitudes on the other. In addition, no significant correlations were found between any of the EABR or EMLR peak amplitudes and speech perception test results. A moderate but significant relation was found between the EALR peak amplitude and speech perception test results. Unlike latencies of earlier peaks, the latency of the EALR peak P2 was significantly related to the speech perception scores.